Pedagogiczny kontekst kategorii sensu życia w okresie średniej dorosłości - Jabłońska, Sylwia (Wydawnictwo Naukowe UAM, 2014)
It is widely believed that stability and permanence of values, purposes and attitudes are the attributes of adulthood. However, the physical and mental changes of middle adulthood as well as social challenges necessitate a search for answers to the emerging existential doubts concerning an overloaded routine of everyday life, a lack of understanding of one’s role in the world, the values themselves, and the meaning of life. This particular development period therefore requires an extra effort and support of the environment; here pedagogy should join as a discipline focused on the theoretical and practical creation of the Human Being of the Future.
Pedagogical Context for the Meaning of Life Category During Middle Adulthood
Keywords: meaning of life; middle adulthood; developmental change; pedagogy; values